Literature Review: Impact of the DASH Diet on Blood Pressure Control in Hypertensive Patients - Comelio, Antonio; Correia, Eduardo; Natalina Dos Santos Sarmento, Remegia; Maria do Rosario da Silva Amaral Pinto, Angela; Lestari, Puji Lestari (Proceedings of Conference on Health Universitas Ngudi Waluyo, 2026)
Hypertension is a major non-communicable disease affecting approximately 1.28 billion adults worldwide and is a primary risk factor for cardiovascular disease, stroke, and kidney failure. The DASH (Dietary Approaches to Stop Hypertension) diet is a non-pharmacological intervention recognized as effective in controlling blood pressure through increased consumption of fruits, vegetables, low-fat dairy, and whole grains while limiting sodium and saturated fat. This systematic literature review aims to analyse the impact of the DASH diet on blood pressure control in hypertensive patients based on evidence from national and international nursing journals published between 2020–2025. Literature searches were conducted through PubMed, Google Scholar, Frontiers in Nutrition, Cambridge Core, JMIR, Scopus, Gizi Indonesia, and Jurnal Manajemen Asuhan Keperawatan using keywords: DASH diet, hypertension, blood pressure, systematic review, nursing. Eleven articles meeting inclusion criteria were analysed using the PRISMA approach. Results showed that the DASH diet consistently reduced systolic blood pressure by 1.29–6.74 mmHg and diastolic blood pressure by 0.76–3.54 mmHg. Effects were enhanced by sodium restriction and feeding-based interventions. Digital health interventions and community nursing education significantly improved patient adherence to DASH. In conclusion, the DASH diet is an evidence-based dietary strategy that should be integrated into nursing care plans for hypertensive patients in both clinical and community settings.